2019
DOI: 10.2152/jmi.66.248
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of large esophageal varices with liver cirrhosis ; a study conducted in Pakistan

Abstract: The assessment of non-invasive parameters for the prediction of large esophageal varices among patients with liver cirrhosisis is of utmost importance. In this study, non-invasive parameters for prediction of large esophageal varices were retrospectively evaluated. The presence of esophageal varices grade III and IV was classified as large esophageal varices positive while no varices or grade I and II were classified as large esophageal varices negative. There were 473 (90.09%) patients with ascites [mild 38 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…There was no significance in total leucocytic count (TLC) between patients with varices and without varices, this came in agreement with the study done by Elatty et al [26]. But in disagreement, the study done by Mahmood et al [27] documented a statistically significant relationship between low WBC and varices presence.…”
Section: Resultssupporting
confidence: 83%
“…There was no significance in total leucocytic count (TLC) between patients with varices and without varices, this came in agreement with the study done by Elatty et al [26]. But in disagreement, the study done by Mahmood et al [27] documented a statistically significant relationship between low WBC and varices presence.…”
Section: Resultssupporting
confidence: 83%
“…We verified the significant association between severity of chronic liver disease and the size of esophageal varices. Patients with large varices mostly belonged to class child B and C. This fact has been validated in previous studies 4,17 . So patients with thrombocytopenia and higher child class are more likely to have large varices and at high risk for upper GI bleed.…”
Section: Discussionsupporting
confidence: 79%
“…In a study done in Pakistan by Mahmood et.al, large varices were found in 47.81% of patients with cirrhosis, and thrombocytopenia was 88.05% sensitive and 59.85% specific for predicting large varices. Lower platelet count showed significant association with large varices 17 . Zubia et al found thrombocytopenia and spleen diameter are significant Indicators for large varices but platelet-count/spleendiameter ratio is definitely more reliable 18 .…”
Section: Discussionmentioning
confidence: 84%
“…Studies indicate that over 80% of patients admitted with ascites have liver cirrhosis as the cause. 5 - 8 Most common cause of cirrhosis in Pakistan is reported as hepatitis C infection in over half of the such patients. 9…”
Section: Burden Of Diseasementioning
confidence: 99%